HUBUNGAN KEWENANGAN ANTARA DPD DAN DPR MENURUT UUD NRI TAHUN 1945 - Ade Kosasih (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2016)
Through the amandement of UUD 1945, it was estabilished a Regional Refresentataives Council or Senate (DPD) beside the Legislative Council or House of Refresentative (DPR). However, the establishing of DPD less to lead the significant changes, it is caused by the limitation of its authority. The limitation of DPD authority has been regulated be fore in UUD 1945. The limitation of DPD authority in legislative side, DPD is not involved to approve the constitution design (RUU) which is inline with the regional authority eventhough the constitution design proposed by DPD, in funding side DPD only has right to consider, mean while on controlling side, all of it controls must be reforted to DPR to be followed up. The asimetric relationship does not reflect the check and balances system in parliament. It is contradicted with the principle of democracy that recuires the functioning of parliament as the refresentatives institution. If it is happen, can caese arrogant, dominant, and the authority monopoliezed by majority groups in DPR. The regulation of DPD authority in the future can be done through the amandemen of UUD 1945. DPD should be gevin the veto right in legislation, and interppelation right, questionnaire and the state the opinion in controlling side. With these right, it is hoped that DPD can become the counterpart for DPR dan President in the paradigm of check and balances, so DPD can its function as regional refresentative productively for strengthening the principle of regional autonomy.